2012
DOI: 10.1111/j.1742-1241.2011.02806.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical efficacy and safety between denosumab and alendronate in postmenopausal women with osteoporosis: a meta-analysis

Abstract: The aim of this study was to perform a head-to-head comparison of efficacy and safety profile between 60 mg denosumab (Den) subcutaneously (SC) per 6 months (Q6M) and 70 mg alendronate (Aln) orally per week (QW) for postmenopausal women with low bone mineral density. We searched electronic databases comparing efficacy and safety of Den SC Q6M and Aln QW in postmenopausal women. The primary outcomes of efficacy evaluation in included trials were incidence of clinical fracture in both groups and bone mineral den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 32 publications
6
38
1
1
Order By: Relevance
“…The data we obtained are consistent with the data obtained by other meta-analyses [28,29]. We can therefore affirm that Denosumab is more efficient than bisphosphonates in increasing the bone mineral density values after 12 months of treatment.…”
Section: Discussionsupporting
confidence: 82%
“…The data we obtained are consistent with the data obtained by other meta-analyses [28,29]. We can therefore affirm that Denosumab is more efficient than bisphosphonates in increasing the bone mineral density values after 12 months of treatment.…”
Section: Discussionsupporting
confidence: 82%
“…Denosumab is a monoclonal antibody to the Receptor Activator of Nuclear factor Kappa B (RANK) ligand, which acts by inhibiting osteoclast formation. While it serves as a potent antiresorptive agent that is more effective than alendronate at increasing BMD (~4%/year), the additional gains (~1%) fall below the threshold of detection in annual DXA exams (2–3% according to the International Society for Clinical Densitometry standards) and are not accompanied by measurably decreased fracture risk [9]. Odanacatib, a new antiresorptive agent that acts by inhibiting cathepsin K, achieved lower (3.5%) increases in BMD in clinical trials than those typically reported for denosumab [10].…”
Section: Current Therapiesmentioning
confidence: 99%
“…No systematic review has yet compared adherence between denosumab and other treatments; the only published data on this issue appear to be from the clinical trials discussed above, suggesting significantly extended time to non-adherence in patients receiving denosumab, relative to those on alendronate 56,57 . A meta-analysis by Lin et al showed that clinical fracture risk and safety concerns did not differ significantly between denosumab and alendronate, although denosumab was significantly more effective than this bisphosphonate at restoring bone mass over 1 year of treatment 61 .…”
Section: Resultsmentioning
confidence: 95%